2022
DOI: 10.3855/jidc.15481
|View full text |Cite
|
Sign up to set email alerts
|

The Tuberculosis and COVID-19 coinfection: A report of two cases at a tertiary referral in Indonesia

Abstract: COVID-19 cases are still rising globally in the middle of the tuberculosis epidemic. Several countries have reported TB-COVID-19 coinfection that could pose a double burden in the health care facilities in developing countries. We reported two pulmonary tuberculosis patients coinfected with COVID-19 with an overlapping clinical manifestation of tuberculosis and COVID-19 with a good prognosis at the end of COVID-19 treatment. This paper aims to discuss TB patients' susceptibility against SARS-COV-2 infection, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The radiological findings of active tuberculosis and COVID-19 are often similar. Isolated upper-lobe pulmonary infiltrates are suggestive of TB, and lower infiltrates of other bacterial infections ( 22 ). Data showed that in almost half of patients co-infected with TB and COVID-19, CT findings were concluded only on COVID-19 ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The radiological findings of active tuberculosis and COVID-19 are often similar. Isolated upper-lobe pulmonary infiltrates are suggestive of TB, and lower infiltrates of other bacterial infections ( 22 ). Data showed that in almost half of patients co-infected with TB and COVID-19, CT findings were concluded only on COVID-19 ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the current Coronavirus diseases-19 (COVID-19) situation, TB patients might be basically susceptible to COVID-19 infection. T-lymphocyte and macrophage depletion in TB patients play an important role in the severe presentation of COVID-19 (39). The crosslink of inflammatory markers such as IL-6 and IL-10 might contribute to the susceptibility of TB COVID-19 coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to COVID-19, tuberculosis is still considered to be a major infectious disease, with 10.6 million newly diagnosed cases and 1.6 million deaths in 2021 [ 5 ]. Amid the COVID-19 epidemic, several countries have reported tuberculosis–COVID-19 coinfection through some studies [ 6 , 7 , 8 ], and increasing numbers of tuberculosis–COVID-19 coinfection cases have been reported. Several reviews and meta-analyses have shown that COVID-19 patients with tuberculosis have a higher risk of death or poorer therapeutic outcomes compared to counterparts without tuberculosis [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%